Evaluation of Community Participation in Community-Based Drinking Water and Sanitation Programs - Trisna Praja, Tondano; Wulan Sumekar Rengganis Wardani, Dyah; Agustina Iryani, Dewi; Prasetyo Wahono, Endro; Setiajaya, Arif; Siti Zulaicha, Annisaa (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
The availability of clean water plays a significant role in fulfilling the need for drinking water and sanitation, which are absolute necessities in human life. The Sustainable Development Goals (SDGs) aim to reduce the proportion of the population without access to safe and sustainable drinking water and basic facilities by half. Access to clean water and sanitation facilities is still tricky in some areas, triggering the implementation of the PAMSIMAS Program. Community involvement is critical to the program's sustainability. This study analyzes the forms and factors supporting and hindering community participation in the PAMSIMAS Program and the environmental benefits of areas that receive the program in Rantau Jaya Ilir village. Central Lampung Regency. This study employs a descriptive qualitative approach, incorporating a SWOT analysis. Planning for community participation in the PAMSIMAS Program is underway. The study shows that community participation can adequately manage the program and meet water needs. Age, gender, level of education, type of work, income, and knowledge are all internal factors. Government policies and regulations play a crucial role as external factors. Based on the research, stakeholders were told to invite the community to each socialization meeting and give suggestions. This way of developing the PAMSIMAS Program community empowerment can be copied and used to create infrastructure development programs in other places. This will help the regional government even more, and the government program for drinking water infrastructure and sanitation is expected to continue and be sustainable so that the infrastructure is kept up and working.